Epistemic communities and social movements: Transnational dynamics in the case of creative commons - Leonhard Dobusch; Sigrid Quack (Max Planck Institute for the Study of Societies, 2008)
While the existence of transnational communities is increasingly recognized in globalization studies, very little is yet known about their impact on global governance. Studies investigating the role of transnational communities in international rule setting tend to specialize in specific types, such as epistemic communities, social movements, or policy networks, and narrow down their effects to agenda setting or issue framing. In this paper, we choose a broader view. We examine the regulatory effects which arise when different types of transnational communities with a common goal operate in concurrence through all phases of the rule-setting process. The empirical research of this papers focuses on the transnational governance field of copyright. More specifically, we study transnational communities aiming to overcome limitations to the prevalent transnational copyright regime in the face of new information technology. On the basis of a longitudinal case study, we show how an epistemic community and a social movement came to interact around the non-profit organization Creative Commons in ways which provided unforeseen momentum for their rule-setting project. This impetus generated both functional and latent effects. While the rapid growth of the social movement enabled Creative Commons to successfully disseminate its private licenses among producers of digital intellectual goods, bypassing classical regulators and policy makers, it also threatened the goals and internal decision making of Creative Commons itself. Following the division of Creative Commons into two separate, but still connected, organizations, it remains to be seen how the interaction of the epistemic community and social movement will evolve in the future. – – Obwohl die Existenz transnationaler Gemeinschaften in der Globalisierungsforschung immer mehr anerkannt wird, bleibt deren Einfluss auf globale Steuerung und Regulierung immer noch größtenteils im Dunkeln. Studien über die Rolle transnationaler Gemeinschaften im Bereich internationaler Regulierung konzentrieren sich meist auf spezifische Typen, wie epistemische Gemeinschaften, soziale Bewegungen oder politische Netzwerke, und beschränken deren Effekte auf Agenda-Setting oder Framing von Themen. In diesem Papier wählen wir eine breitere Perspektive. Wir untersuchen regulatorische Effekte, die entstehen, wenn verschiedene Typen von transnationalen Gemeinschaften mit einem gemeinsamen Ziel gleichzeitig sämtliche Phasen des Regulierungsprozesses durchlaufen. Der empirische Teil des Papiers konzentriert sich auf transnationale Regulierung im Bereich des Urheberrechts. Konkret untersuchen wir transnationale Gemeinschaften, die Beschränkungen des vorherrschenden Urheberrechtsregimes angesichts neuer Informationstechnologie zu überwinden suchen. Auf Basis einer Längsschnittstudie zeigen wir, wie eine epistemische Gemeinschaft und eine soziale Bewegung rund um die gemeinnützige Organisation Creative Commons interagieren und so unvorhergesehenen Schwung in ihrem Regulierungsprojekt auslösen. Diese Dynamik erzeugte funktionale ebenso wie verborgene Effekte. Während das schnelle Wachstum der sozialen Bewegung die erfolgreiche Diffusion von den privaten Lizenzen von Creative Commons vorbei an klassischen Regulierern und politischen Akteuren unter Erzeugern von digitalen intellektuellen Gütern ermöglichte, bedrohte es Ziele und interne Entscheidungsstrukturen von Creative Commons selbst. Wie sich das Zusammenwirken von epistemischer Gemeinschaft und sozialer Bewegung nach der Teilung von Creative Commons in zwei getrennte, aber immer noch miteinander verknüpfte Organisationen weiterentwickelt, wird erst die Zukunft zeigen.
Keywords: 300